Prevalence of non-suicidal self-injury in medical students of Rawalpindi; its socio-demographics, methods, and functions - Mehmood, Muzna; Awan, Noor-ul-ain; Fiaz, Tooba; Raza, Syeda Aliya (Journal of the Pakistan Medical Association, 2023)
Objective: To investigate the prevalence of non-suicidal self-injury among Pakistani medical students, its association with demographic variables, and the distribution of its methods and functions. Method: The cross-sectional study was conducted in from April 2021 to March 2022 at Rawalpindi Medical University, Rawalpindi, Pakistan, and comprised medical students regardless of gender and year of study. Data was collected using the inventory of statements about self-harm scale to assess their socio-demographics, non-suicidal self-injury behaviors and functions. Data was analyzed using SPSS 28. Results: Of the 411 subjects approached, 386(94%) correctly filled the forms; 170(44%) males and 216(55.9%) females. The overall mean age was 19.7 ±1.5 (range: 17-27 years). There were 132(34.1%) students from first year, 146(37.8%) second year, 44(11.3%) third year, 54(13.9%) fourth year and 10(2.5%) from the final year. There were 110(28.4%) with non-suicidal self-injury; 60(54.5%) males and 50(45.4%) females (p=0.008). There were 18(4.7%) subjects aged 18 years, and, of them, 14(77.7%) exhibited self-harm behavior. Among specific non-suicidal self-injury behaviors, ‘interfering with scabs and wound healing’ was the most common method 80(72.7%). As for the functions of non-suicidal self-injury behavior, there was a significant difference between intrapersonal and interpersonal functions (p<0.05). Conclusion: Non-suicidal self-injury was highly prevalent among the young subjects, and it needs proper intervention for timely management. Key Words: Behavior, Behavior mechanisms, Pakistan, Personality inventory, Self-injurious behavior, Young adult.